CERPEN ANTOLOGY ANALYSIS "1 WOMEN 14 MEN WORKS DJENAR MAESA AYU" (A DISCUSSION OF FEMINISM AND EDUCATION VALUE) - Sutrimah, Joko (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2017)
This research is aimed at knowing the existence and emancipation of women, in other words the equality with men to obtain education to the highest level is worthy of him. In the woman appeared a desire to excel in realizing her abilities according to the knowledge and skills she had learned. Women want to take part in the public sphere in order to actualize themselves. The usefulness of this research is to find out how the perspective of feminism in the world of literature can provide benefits for students and teachers of Indonesian language and literature in literary learning, especially feminism short stories.This type of research is qualitative, the source of this research data is the results of the study of documents and field notes (fieldnotes) which consists of two parts, namely the description and reflection section. Data collection techniques used were 1. Interactive techniques and 2. Techniques Note that researchers used data triangulation to collect the same data, the data analysis technique used in this study used content analysis method.